SYNTHESIS AND INVESTIGATION OF SUPERCONDUCTING CUPRATE Y2BA5CU7O15,7: UDC 546.43'56'64+538.945 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
The results from investigations into the structure, electrical and crystallographic properties of new high-temperature superconducting phase of Y2Ba5Cu7O15,7. The superconducting sample was synthesized by means of solid state reaction. The synthesis has been controlled by infrared spectroscopic analysis. Established that the compound gradually removed water and carbonates after calcination for 24 hours at a temperature of 950 °C. The phase composition of the compound was determined by X-ray powder diffraction. Indexing X-ray, determination of spatial and crystallographic parameters were set by INDEX and X-Ray. The sample consist of superconducting phase and non-superconducting phase. The superconducting phase Y2Ba5Cu7O15,7 was orthorhombic structure and Pmm2 space group symmetry. The criterion of orthorhombicity equal σ=0,574. The Pmm2 space group was fit well on superconducting phase with the lattice parameters as a=3,811Å, b=3,855Å and c=26,532Å. The non-superconducting phase corresponds to BaCuO2,5 with Im-3m space group. Nonstoichiometric oxygen and the average oxidation state of copper content were determined of iodometric titration. Accordingly, the nonstoichiometric oxygen and the average oxidation state of copper equal 15.7 and 2.20 respectively. Specific electric resistance of the sample were measured by the method of four-contact. . In the normal state resistivity of the sample varies little with temperature. However, resistance shows a weak dependence of the semiconductor value at room temperature 4,6mΩcm. Beside this, were found the superconducting transition: start and end critical temperature that are 85K and 80K respectively and width superconducting transition which is ΔTc = Tc (on) -Tc (off) = 5K.
Keywords: superconducting cuprate, solid-phase synthesis, IR spectroscopy, x-ray diffraction, superconducting properties